PERHITUNGAN TARIF IMBAL JASA KAFALAH PENSIUN DAN PRAPENSIUNAN BERBASIS WEB PADA PT. PENJAMINAN JAMKRINDO SYARIAH CABANG PALEMBANG - Jemakmun Jemakmun; Arie Nardu (Direktorat Riset dan Pengabdian Pada Masyarakat (DRPM) Universitas Bina Darma, 2021)
PT Penjaminan Jamkrindo Syariah then abbreviated as PT Jamkrindo Syariah was born from the Sharia Guarantee Division which is a Sharia Business Unit in the Indonesian General Credit Guarantee Company. The problem that arises in the guarantor company is the difficulty in calculating the price of the Kafalah fee when outside the office if it has to do calculations in the office making prospective customers feel the service provided is slow and unable to compete with other competitors, so we need an application that can help sales in calculating the cost of a Kafalah fee if it is outside the office so the calculation process is fast. The application that will be built is a web-based application software and uses the Prototype method.